Annular region containing all the zeros of lacunary-type polynomials - Kumar, Ashish; Manzoor, Zahid; Zargar, Bashir Ahmad (Armenian Journal of Mathematics, 2022)
In this paper, we find the annular region containing all the zeros of lacunary-type polynomials, whose coefficients are subjected to certain restrictions.
Keywords: Lacunary-type polynomial; Eneström-Kakeya theorem